2017
DOI: 10.1155/2017/1064863
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Special Phase Transformation of Hydrophilic Iron Oxides Nanoparticles

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs), -Fe 2 O 3 , with hydrophilic surfaces are fabricated in ethylene glycol solutions, without surfactant or additive, by solvothermal process from -Fe 2 O 3 nanoparticle as precursors. With the addition of a trace of hydrazine hydrate, the cubic phase Fe 3 O 4 nanoparticles are obtained instead of -Fe 2 O 3 . The saturation magnetization value of -Fe 2 O 3 nanoparticles is up to 74.3 emu/g. This study provides a low cost, safe, and universal route to serve as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Thus, the magnetite formed from DES extracted coconut shell is superparamagnetic in nature [34]. This nature is in line with other studies made by previous researchers [27,31,35]. The average zeta potential of iron oxide nanoparticles was À7.305 mV.…”
Section: Characteristic Of Green Synthesized Magnetic Iron Nanoparticlessupporting
confidence: 88%
“…Thus, the magnetite formed from DES extracted coconut shell is superparamagnetic in nature [34]. This nature is in line with other studies made by previous researchers [27,31,35]. The average zeta potential of iron oxide nanoparticles was À7.305 mV.…”
Section: Characteristic Of Green Synthesized Magnetic Iron Nanoparticlessupporting
confidence: 88%
“…Therefore, eco-friendly synthesis, as well as a low-toxicity, low-cost, and more facile process, are obtained. For instance, a facile one-step hydrothermal approach, facile microwave-assisted synthesis, facile coprecipitation methods using poly­(vinyl alcohol) (PVA) as a capping agent under alkaline condition, synthesized process under sunlight, the utilization of ethylene glycol solutions which result in the absence of surfactant or additive used during the synthesis process, synthesize methods by simple precipitation of Fe­(II) and Fe­(III) salts in an aqueous ammonia solution through the addition of polyethylenimine (PEI), etc.…”
Section: Advance Fabrication Of Nanometer-sized Iron Oxides From Natu...mentioning
confidence: 99%
“…Iron oxides are chemically stable and naturally abundant, and they could be categorized as ancient materials,which have been utilized a long time for some applications, such as application for tools and weapons in the Iron Age. Nowadays, in nanometer size, iron oxides have been well-developed and synthesized using various methods in the forms of low-dimensional material forms; zero, one, two, and three-dimensional (0D, 1D, 2D, and 3D, respectively). Each nanometer-sized iron oxides form has its specialty, such as 0D and 3D iron oxides are suitable in biomedical and environmental applications. ,, Although, iron oxide in the form of 0D is still blurred with their exact size, because the obtained 0D iron oxides sizes was mostly reported almost similar to iron oxide in 3D nanoparticles. As for iron oxides in 1D form, many previous studies have been reported.…”
Section: Introductionmentioning
confidence: 99%